STRATEGI KOMUNIKASI PEMASARAN SONGKET PANDAI SIKEK PADA PANDEMI COVID-19 - Siska Mitria Nova; Mutia Kahanna; Wirda Hayani (Relief : Journal of Craft, 2022)
ABSTRACT Songket Pandai Sikek is a songket that has been traded in the market. Pandai Sikek is one of the nagari in the Minangkabau which a famous because pandai sikek songket is producer in West Sumatra. The spread of the Covid-19 virus has a negative impact on various economic sectors. The spread of covid -19 has caused a decrease in market demand for the sikek songket. The COVID-19 outbreak requires changes in marketing communication strategies for business players can survive during of a pandemic. The selection of a marketing communication strategy is one of the efforts made so that the business activities of the songket pandai sikek can survive during the COVID-19 pandemic. The purpose of this study is to identify and determine the choice of an integrated marketing communication strategy that is in accordance with market needs during of the covid-19. The method used in this research is a qualitative method with a descriptive type of research. The results of the research, integrated marketing communication strategy used during the covid-19 pandemic used by the songket pandai sikek business players is interactive marketing.